The Role Of Teachers In Improving Students' Learning Motivation At Abata Ceria Paud, Ten Iga Village In The 2024/2025 Academic Year - Hartini, Susi; Mahendra, Juandra Prisma; Eliyana, Eliyana (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract. This study aims to determine the role of teachers in increasing student learning motivation at Paud Abata Ceria, Teniga Village, in the 2024/2025 academic year, where in increasing this motivation teachers use strategies so that students are more enthusiastic about learning. This type of research is qualitative research with a descriptive approach, data collection techniques used in this study are observation, interviews and documentation. The information collected comes from the principal and teachers at the school. The data analysis technique used in this study is through several stages including 1) data condensation. 2) data display. 3) drawing conclusions.The results of this study are the role of teachers in increasing student learning motivation which describes (1) teacher strategies in increasing student learning motivation according to their roles, namely a). teachers as demonstrator by providing appropriate learning methods, paying attention to student concentration. b). Teachers as mediators by providing learning media. c). Teachers as evaluators by giving prizes, giving grades, praise. (2) The impact of the role of teachers in increasing student learning motivation is that students are more enthusiastic in learning, increasing self-confidence, students are more independent.Keywords: Teacher Role, Learning Motivation